Pengaruh penggunaan Buku Dasar-Dasar Mustaqilli 1 Terhadap Keterampilan Membaca dan Menulis Bahasa Arab MTs DDI Ainus Syamsi Makassar - Salihat, Nurjamila; Muhammad Shabir U; Asriyah (Universitas Islam Negeri Alauddin, 2025)
The problem in this research is that the Arabic language teaching and learning process, especially Arabic reading and writing skills, is still low, due to the background of each individual. By overcoming these problems, teaching materials were selected, namely, the mustaqilli basics book, with the aim of finding out the effect of using the mustaqilli basics book 1 on the Arabic reading and writing skills of MTs DDI Ainus Syamsi Makassar students. This research is experimental research with a positivistic, quantitative approach. The research design is a pretest-posttest control group. The research population was 45 people and the sample was determined to be 35 people. The instrument used is a test which is analyzed using descriptive statistics and inferential analysis. The research results show the effect of using the Mustaqilli Basics 1 book on students’ Arabic reading and writing skills in the experimental class and control class at Mts DDI Ainus Syamsi Makassar, by testing the hypothesis using an independent simple test to make decisions. So, a sig value of 0.000 <0.05 is obtained. Therefore, it is stated that H0 is accepted and Ha is rejected. The effect of using the Mustaqilli Basics 1 book on the Arabic writing skills of students in the experimental class and control class at Mts DDI Ainus Syamsi Makassar, obtained a sig value of 0.000 < 0.05. Therefore, it is stated that H0 is accepted and Ha is rejected.